2011
DOI: 10.1103/physreve.84.016213
|View full text |Cite
|
Sign up to set email alerts
|

Isochronal chaos synchronization of delay-coupled optoelectronic oscillators

Abstract: We study experimentally chaos synchronization of nonlinear optoelectronic oscillators with time-delayed mutual coupling and self-feedback. Coupling three oscillators in a chain, we find that the outer two oscillators always synchronize. In contrast, isochronal synchronization of the mediating middle oscillator is found only when self-feedback is added to the middle oscillator. We show how the stability of the isochronal solution of any network, including the case of three coupled oscillators, can be determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Interestingly, this phenomenon could explain the occurrence of identical synchronization between widely separated cortical regions of the human brain despite of synaptic/dendritic delays [2][3][4][5]. ZLS has also been experimentally demonstrated in delay coupled semiconductor lasers [6], optoelectronic oscillators [7] and in low-dimensional delay coupled chaotic electronic circuits (without intrinsic time-delay) [8] via dynamical relaying. Recently Banerjee et al reported that the coupling threshold for ZLS between the outermost identical oscillators decreases when an impurity (parameter mismatch) is introduced in the relay unit [9].…”
Section: Introductionmentioning
confidence: 88%
“…Interestingly, this phenomenon could explain the occurrence of identical synchronization between widely separated cortical regions of the human brain despite of synaptic/dendritic delays [2][3][4][5]. ZLS has also been experimentally demonstrated in delay coupled semiconductor lasers [6], optoelectronic oscillators [7] and in low-dimensional delay coupled chaotic electronic circuits (without intrinsic time-delay) [8] via dynamical relaying. Recently Banerjee et al reported that the coupling threshold for ZLS between the outermost identical oscillators decreases when an impurity (parameter mismatch) is introduced in the relay unit [9].…”
Section: Introductionmentioning
confidence: 88%
“…Recently, this structure of the MSF was confirmed experimentally [33] and even utilized to predict the synchronizability of a network from a simpler motif [33,34].…”
Section: Synchronization Of Delay-coupled Systemsmentioning
confidence: 73%
“…Besides zero-lag synchronization, a state where all nodes undergo the same dynamics without a phase shift, group and cluster synchronization have received growing interest both in theory [Sorrentino and Ott, 2007;Kestler et al, 2007Kestler et al, , 2008Dahms et al, 2012;Kanter et al, 2011b,a;Golubitsky and Stewart, 2002;Lücken and Yanchuk, 2012;Sorrentino, 2014;Pecora et al, 2014;Poel et al, 2015] and in experiments [Illing et al, 2011;Aviad et al, 2012;Blaha et al, 2013;Williams et al, 2012Williams et al, , 2013aRosin, 2015]. In the case of group synchrony, the network consists of several groups where the nodes within one group are in zero-lag synchrony Dahms et al, 2012].…”
Section: Dynamics On Networkmentioning
confidence: 99%
“…Recently, more complex synchronization patterns, including cluster and group synchronization, have received growing interest both in theory [Sorrentino and Ott, 2007;Kestler et al, 2007;Ashwin et al, 2007;Kestler et al, 2008;Kori and Kuramoto, 2001;Lücken and Yanchuk, 2012;Dahms et al, 2012;Kanter et al, 2011b,a;Golubitsky and Stewart, 2002;Sorrentino, 2014;Pecora et al, 2014;Poel et al, 2015] and in experiments [Illing et al, 2011;Aviad et al, 2012;Blaha et al, 2013;Rosin et al, 2013;Williams et al, 2012Williams et al, , 2013aRosin, 2015]. These scenarios appear in many biological systems, examples include dynamics of nephrons [Mosekilde et al, 2002], central pattern generation in animal locomotion [Ijspeert, 2008], or population dynamics [Blasius et al, 1999].…”
Section: Cluster and Group Synchrony: The Theorymentioning
confidence: 99%
See 1 more Smart Citation